A Case of Intracardiac Extension of Small Cell Carcinoma Demonstrated on F-18 FDG PET/CT - Wang, Jiaqiong; Maresky, Hillel; Yu, Jian Q; Cohen., Gary (Archives of Clinical and Medical Case Reports, 2024)
A 64 year-old male patient with 40 pack year history of smoking presented with hemoptysis and shortness of breath. CT demonstrated perihilar right upper lobe soft tissue mass with tumor invasion into the right mainstem bronchus, and invasion into the right superior pulmonary vein with tumor thrombus extending into the left atrium. Subsequent F-18 FDG PET/CT showed a large hypermetabolic right upper lobe mass invading into the right mainstem bronchus and the right superior pulmonary vein with tumor thrombus extending into the left atrium. The patient underwent bronchoscopy, and biopsies of the right upper lobe revealed small cell carcinoma.